Development and evaluation of a hand-held fiber-optic Raman probe with an integrated autofocus unit - Yang, Wei; Knorr, Florian; Popp, Juergen; Schie, Iwan W. (Optics Express, 2020)
Current implementations of fiber-optic Raman spectroscopy probes are frequently based on non-contact probes with a fixed focus and thus and have to precisely maintain the probe-to-sample distance to ensure a sufficient signal collection. We propose and experimentally demonstrate a novel hand-held fiber-optic Raman probe design, which is based on a liquid lens autofocusing unit, combined with a distance sensor and an in-house developed algorithm to precisely determine the probe-to-sample distance. The reported probe significantly improves the signal stability even for hand-held operation, while reducing distance-dependent artifacts for the acquisition of Raman spectra and can improve the acquisition of Raman spectra in a variety of applications.
CRIS-Team Scopus Importer:2023-04-20